Characterization of Inkjet Printed Electrodes with Improved Porosity. (7th July 2017) - Shukla, Shantanu; Stanier, David; Saha, Madhu S; Zahiri, Beniamin; Tam, Mickey; Stumper, Jürgen; Secanell, Marc
Abstract : Propylene glycol was used as an additive to enhance the porosity and performance of catalyst layers (CL) fabricated using inkjet printing. Compared to the previously used additive, ethylene glycol based ink, the modified recipe helped in improving the CL porosity by 10 - 20% and the in-situ performance by 50-100 mV at high current densities. The performance for PG based CLs was found to increase with decreasing ionomer/carbon (I/C) ratio, with I/C ratio of 0.5 showing the best performance. A setup based on Archimedes principle is used to measure the CL porosity, that is based on weighing the sample in n-octane and deionized water to determine the solid and bulk volumes respectively. Overall, the work improves on the previously reported inkjet printed CL performance and addresses the concern of low porosity by modifying the ink recipe.